1996
DOI: 10.1109/10.532121
|View full text |Cite
|
Sign up to set email alerts
|

Microwave tomography: two-dimensional system for biological imaging

Abstract: Microwave tomographic imaging is one of the new technologies which has the potential for important applications in medicine. Microwave tomographically reconstructed images may potentially provide information about the physiological state of tissue as well as the anatomical structure of an organ. A two-dimensional (2-D) prototype of a quasi real-time microwave tomographic system was constructed. It was utilized to reconstruct images of physiologically active biological tissues such as an explanted canine perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(72 citation statements)
references
References 9 publications
0
67
0
1
Order By: Relevance
“…It is well known that, as diffraction and scattering phenomena at microwave frequencies are relevant, the sliced approach does not permit to obtain quantitative reconstructions [10,11]. However, it has been also shown, by numerical examples, that it allows to localize and to roughly retrieve the silhouette of elongated scatterers [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that, as diffraction and scattering phenomena at microwave frequencies are relevant, the sliced approach does not permit to obtain quantitative reconstructions [10,11]. However, it has been also shown, by numerical examples, that it allows to localize and to roughly retrieve the silhouette of elongated scatterers [12].…”
Section: Introductionmentioning
confidence: 99%
“…The electronic tissue details can provide histological and pathological information non-invasively and in-vivo. The mechanism of action relies on the cellular components' dielectric properties that will influence the wave propagation and hence act as a sensing mechanism (Semenov et al, 1995, Semenov et al, 1996. Spectroscopic imaging for all wavelength ranges uses the alteration in the spectral structure of the input signal both in the time and frequency domain as a result of interaction with the biological medium.…”
Section: Examples Of Available Imaging Applicationsmentioning
confidence: 99%
“…Also, microwave imaging is a non-ionizing method which probably will be rather inexpensive compared to MRI and safer compared to X-ray. Versions of video pulse radars were first introduced for medical applications as a means to detect malignancy in internal biological tissues by Hagness et al [8][9][10]. Fear et al [11][12][13] demonstrated the feasibility of detecting and localizing small tumors in three dimensions.…”
Section: Introductionmentioning
confidence: 99%